D1.1 Work schedule - Hadjimitsis, Diofantos G.; Lysandrou, Vasiliki; Agapiou, Athos; Lasaponara, Rosa; Masini, Nicola; Schreier, Gunter (My University, 2016)
The specific report aims to present all the activities and due times of delivery to be carried out through the three years of ATHENA project. This report represents a basic programming reference document for the future actions of the project. Further detailed discussions on work planning were held at the kick-off meeting held in Limassol – Cyprus at the premises of Cyprus University of Technology in December 2015.
Keywords: ATHENA project; Activities